A new furanoxanthone from Garcinia mangostana - Ee, Gwendoline Cheng Lian; See, Irene; Teh, Soek Sin; Daud, Shaari (Taylor & Francis, 2014)
Our phytochemical study on the stem bark of Garcinia mangostana has led to the discovery of a new furanoxanthone, mangaxanthone A (1), together with five known analogs. The five known analogs that were isolated are α-mangostin (2), β-mangostin (3), cowagarcinone B (4), and dulcisxanthone F (5). The structural elucidations of these compounds were carried out by interpreting their spectroscopic data, mainly 1D and 2D NMR spectra and MS.